OPPORTUNITIES OF TOURIST SERVICES THROUGH MOBILE APPLICATIONS (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article analyzes the role and significance of mobile applications in the tourism sector and the conveniences they provide in serving tourists. Mobile apps enable tourists to book hotels, purchase transportation tickets, access guide services, and obtain other tourism-related services. The paper examines development trends in Uzbekistan in this field and highlights existing challenges.